ANALISIS KEBUTUHAN MAHASISWA TERHADAP BAHAN AJAR DALAM PEMBELAJARAN MITIGASI BENCANA - Devicawati, Devicawati; Karyadi, Bhakti; Johan, Henny; Farid, Muhammad; Winarni, Endang Widi (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This study aims to analyze students' needs for teaching materials in disaster mitigation learning. This research method uses quantitative descriptive research. Then analyzed and described to answer the existing problems. The subjects of the study were 53 students of the Science Education study program, University of Bengkulu, semester V. The instrument used was a questionnaire, with 3 aspects (disaster mitigation, teaching materials and learning process) and 24 questions. The results of the analysis showed that 95% of students chose the need for education about natural disaster mitigation. 11% of students did not know the Evacuation Location (gathering point) for the earthquake disaster at the University of Bengkulu and 22% of students did not know the flow map showing evacuation signs at the University of Bengkulu, so teaching materials that contain this are needed. The teaching materials needed by students are interactive and easy-to-use teaching materials, the contents of the material are clearly described in accordance with the facts in life, teaching materials that are audio-visual based (there are videos and animations), equipped with things that need to be considered in disaster mitigation and have a suitable color combination.